2015
DOI: 10.5430/wje.v5n6p37
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Principals’ Physical Education Perceptions and Views from Elementary and Middle Schools of Shanghai

Abstract: This study examined the status of principals' physical education (PE) perceptions, the differences between gender and school-levels of these principals' PE perceptions; and what they have to say about the opportunities, challenges and solutions on their school PE. Participants were 92 principals (37 Males, 55 Females) from 12 different school districts of Shanghai. The Adapt Principal Perception on PE Questionnaire Chinese Version (APPPEQ C.V.) was employed for data collection; this questionnaire consists of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…These results support the findings of others (Amis et al, 2012;Bechtel & O'Sullivan, 2007;Faucette & Graham, 1986;Lounsbery, McKenzie, Trost, & Smith, 2011;Meredeth & Curtner-Smith, 2017;Sallis et al, 1996;Zeng & Wang, 2015) and emphasize the significant role principals can have on PE programs. Apart from the constraints of facilities, tight budgets, public policies, a lack of proper facilities, and so on, there is HOPE (Sallis et al, 2012) that we can achieve the many benefits of quality PE with the support of principals, colleagues, and students (Bechtel & O'Sullivan, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results support the findings of others (Amis et al, 2012;Bechtel & O'Sullivan, 2007;Faucette & Graham, 1986;Lounsbery, McKenzie, Trost, & Smith, 2011;Meredeth & Curtner-Smith, 2017;Sallis et al, 1996;Zeng & Wang, 2015) and emphasize the significant role principals can have on PE programs. Apart from the constraints of facilities, tight budgets, public policies, a lack of proper facilities, and so on, there is HOPE (Sallis et al, 2012) that we can achieve the many benefits of quality PE with the support of principals, colleagues, and students (Bechtel & O'Sullivan, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The perception of principals (Zeng & Wang, 2015) complicates matters for physical educators. Few consider teaching PE a badge of distinction or a subject matter that will make a difference to students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking through Schlecty's (2015) preachment, practice, pretests framework, our results point out much preachment, very strong pretests and minimal practice because in narrative neither administrators nor teachers question and deny the significance of the physical education course. This finding is supported by previous studies (e.g., Varol, 2014;Zeng & Wang, 2015) that found that school principals' self-reported perceptions are very positive. It is understandable that selfreports confirm the preachments.…”
Section: Discussion a N D Conclusionsupporting
confidence: 89%
“…Also, while much research focuses on PE courses at higher education and teacher education programs (Hayes, Capel, Katene, & Cook, 2008;Kim, Cardinal, & Cardinal, 2015;Engstrom, 1999), there remains a paucity of evidence on K-12 PE courses. Studies on attitudes towards PE courses are focused on teachers' perspectives (Bozoglu & Göktürk, 2016;Gordon, Dyson, Cowan, McKenzie, & Shulruf, 2016;Marinsek & Kovac, 2019;Simmons & MacLean, 2018), students' perspective (Mercier, Donovan, Gibbone, & Rozga, 2017;Mohammed & Mohammad, 2012;Phillips & Silverman, 2015), administrators' perspective (Oh & Graber, 2019;Zeng & Wang, 2015) or parents' (Nisskaya, 2018). However, there has been no study to date that presents an in-depth comprehensive exploration of PE courses at K-12 level through a consolidation of perspectives of various stakeholders (teachers, academics, athletes, coaches).…”
Section: Introductionmentioning
confidence: 99%